Independent prescriber physiotherapist led balance clinic: the Southport and Ormskirk pathway. Issue 5 (16th February 2017) - Burrows, L; Lesser, T H; Kasbekar, A V; Roland, N; Billing, M
Abstract: Objective: To report the introduction and impact of non-medical prescribing, initiated to improve patient pathways for those presenting with dizziness and balance disorders. Methods: The Southport and Ormskirk physiotherapy-led vestibular clinic sees and treats all patients with dizziness and balance disorders referred to the ENT department. Letters are triaged by an audiologist, who also performs an otological examination and hearing test; this is followed by an assessment with the independent prescriber physiotherapist. An ENT consultant is nearby if joint consultation is needed. Diagnoses, treatments and patient satisfaction were studied, with an analysis of the impact of medication management (stopping or starting medicines) on patients and service. Results: In 12 months, 413 new patients with dizziness and balance disorders had appointments. The most common diagnoses were benign paroxysmal positional vertigo and vestibular migraine. Eighty-four per cent of patients required self-management strategies, 50 per cent exercise therapy, 48 per cent medication management and 24 per cent a particle repositioning manoeuvre. Patient satisfaction was high (99 per cent). Conclusion: Having an independent prescriber physiotherapist leading the balance clinic has reduced the number of hospital visits and onward referrals. Nearly half of all patients required medication management as part of their dizziness or balance treatment.